DISCRIMINATION AS REFLECTED IN KENNETH REXROTH’S “DISCRIMINATION” - Satria, Rahadian (LANTERN (Journal on English Language, Culture and Literature), 2014)
The purpose of this thesis is to find out how discrimination happens in society and causes a lot of horrible effects to people. This final paper uses the intrinsic elements such as imagery to imagine the detail of discrimination in Rexroth’s “discrimination”. The writer also used library research in collecting the data. In analyzing the extrinsic elements, the writer used Racism and Discrimination concepts to see that there were indications of racist and discriminative behavior in this poem. The result of this academic paper shows that discrimination is still common in the society because of many things especially racism.Keyword: discrimination, racism, society, hypocrisy, imagery